The Effect of Air Pollution on Malondialdehyde, Superoxide Dismutase, and Lung Function of Traffic Police in Banjarbaru City - Supianti Agustina; Isa Ansori; Meitria Syahadatina Noor (JURNAL INFO KESEHATAN, 2025)
Air pollution has a significant impact on lung health, especially for groups of workers who are directly exposed to pollution, such as traffic police. This study aims to evaluate the effect of air pollution on Malondialdehyde (MDA), Superoxide Dismutase (SOD), and lung function levels in traffic police in Banjarbaru City. The method used was observational analytic with a cross-sectional research design. This study involved two groups, namely traffic police and non-traffic police, with a purposive sampling technique. The subjects involved totaled 80 people, divided into 40 traffic police and 40 non-traffic police, with the criteria of traffic police who have worked for at least 5 years. Serum MDA and SOD levels and pulmonary function assessment using spirometry were performed in both groups. The results showed that MDA levels in traffic police were higher (184.75 ± 14.5 µM) compared to non-traffic police (178.4 ± 3.4 µM), while SOD levels in traffic police were lower (1.06 ± 0.384 units) compared to non-traffic police (1.22 ± 0.3 units). In addition, Forced Vital Capacity (FVC) and Forced Expiratory Volume in one second (FEV1) values in traffic police were lower, while the FEV1/FVC ratio showed no significant difference. Air pollution has a significant effect on increasing MDA, decreasing SOD, FVC, and FEV1 in traffic police. It is recommended to reduce air pollution exposure in this group through stricter pollution control policies and the use of respiratory protective equipment.